2018
DOI: 10.1007/s00253-018-9247-3
|View full text |Cite
|
Sign up to set email alerts
|

O2 versus N2O respiration in a continuous microbial enrichment

Abstract: Despite its ecological importance, essential aspects of microbial N2O reduction—such as the effect of O2 availability on the N2O sink capacity of a community—remain unclear. We studied N2O vs. aerobic respiration in a chemostat culture to explore (i) the extent to which simultaneous respiration of N2O and O2 can occur, (ii) the mechanism governing the competition for N2O and O2, and (iii) how the N2O-reducing capacity of a community is affected by dynamic oxic/anoxic shifts such as those that may occur during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…These characterizations were used to correlate changes in community composition with changes in observed bioreactor performance (34). The Particle Filter implementation demonstrated here, was used to reconstruct the respiration rates in a wide range of dynamically operated bioreactors, varying from aerobic pulse-fed bioreactors (34), anaerobic bubble columns (37), anoxic N 2 O respiration (38), aerobic/anaerobic fermentations (39), isotope labeled studies for identification of novel pathways (40), and in chain elongation studies (41). The applicability of this reconstruction tool contributes to the identification of functional properties of biological processes in dynamic environments.…”
Section: Discussionmentioning
confidence: 99%
“…These characterizations were used to correlate changes in community composition with changes in observed bioreactor performance (34). The Particle Filter implementation demonstrated here, was used to reconstruct the respiration rates in a wide range of dynamically operated bioreactors, varying from aerobic pulse-fed bioreactors (34), anaerobic bubble columns (37), anoxic N 2 O respiration (38), aerobic/anaerobic fermentations (39), isotope labeled studies for identification of novel pathways (40), and in chain elongation studies (41). The applicability of this reconstruction tool contributes to the identification of functional properties of biological processes in dynamic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that these differences may be of a quantitative rather than qualitative nature, reflecting changes in the proportion between electron transfer capabilities of the reducing and oxidizing branches of the respiratory chain. Conthe et al [ 33 ] related the preferential use of O 2 over N 2 O observed in a natural mixed culture to the fact that the Monod half-saturation constant ( K s ) value for O 2 was 1-2 orders of magnitude smaller compared to K s (N 2 O). Although we found a clear association between deletion of the high-affinity oxidase and appearance of aerobic denitrification, the explanation based on the change in affinity for oxygen does not apply in our case because the effect of oxidase deletion persists even at high oxygen concentrations that saturate all terminal oxidases present.…”
Section: Discussionmentioning
confidence: 99%
“…Organic matter additions have been the focus of many N 2 O management studies (Hellman et al, 2019; Lazcano et al, 2021; Senbayram et al, 2012; Stevenson et al, 2011; Sutton‐Grier et al, 2011; Wang, Amon, et al, 2021; Wu et al, 2018). N 2 O consumption is primarily an anaerobic, respiratory pathway (Hein & Simon, 2019; Shan et al, 2021), and so there exists an environmental correlation where N 2 O consumption rates are highest when both O 2 concentrations are low and organic matter abundance is high (Conthe et al, 2018; Senbayram et al, 2012; Wu et al, 2013, 2018). However, studies have found that the net emission of N 2 O can go either up or down, depending on the soil and the nature of the organic matter addition.…”
Section: Introductionmentioning
confidence: 99%